Attitudes and barriers of medical students towards conducting research in a medical college - Narasimhaiah, Manjunath G.; Mallikarjuna, Swamy R.; Kalaburgi, Riyaj A. (International Journal of Basic & Clinical Pharmacology, 2020)
Background: It is well known that evidence-based medicine is the rule for clinical practice. This can be enhanced by conducting good research. Medical students being the future doctors should contribute significantly. But the research among the medical students is very poor with respect to presentations and publications. In view of this data the study was done to know their perception, attitude and barriers for conducting research. Methods: This was a cross sectional observational study involving three different batches of medical students by giving a semi-structured questionnaire. Results: The response among the participants to involve in research was only 30%. Among them the overall attitude and barrier score were 3.69±0.29 and 3.63±0.42 respectively with statistical significance shown between genders and not between batches. The biggest barrier was lack of previous research experience (91.67%). The most common motivational factor was self-interest (90.7%). Conclusions: If given sufficient training and facilities provided, we should be able to get more research among the medical students.